Analysis of Magnetostrictive Microactuators - Albach, Thorsten; Sutor, Alexander; Lerch, Reinhard; Sutor, Alexander (Technisches Messen, 2010)
The magnetostrictive effect offers new possibilities to design actuators for microsystems (MEMS). Especially monomorph-bending-cantilever-type microactuators can be used for many interesting applications. These actuators are excited to bending movements under the influence of external magnetic fields We present calculation methods, the fabrication process, and the measuring technology to enable the design of microsystems based on these actuators. The focus of this study is on the analysis of the mechanical eigenfrequencies and the characteristic magnetostrictive curves. Based on the results, our calculation methods as well as the reproducibility of our fabrication process are verified. Linear sections of the characteristic curves can be found using the data obtained.
Keywords: MEMS; microactuator; magnetostriction